Rancang Bangun Mini Trainer Temperatur Sensor Berbasis Arduino Sebagai Media Pembelajaran - Refi Putra Yandi; Irma Yulia Basri (Universitas Negeri Padang, 2021)
The Department of Automotive Engineering, FT UNP, has incomplete learning media to support lectures on Sensor and Transducer theory such as trainers or teaching aids. This study uses the Research and Development method in the field of education, aims to determine the performance, the feasibility level of the temperature sensor trainer as a learning medium. Data were collected by several stages of testing: accuracy test, linearity test, repeability test and feasibility test for media experts and users. The temperature sensor trainer is effectively used after the Accuracy Test is carried out with a measurement accuracy value of 100%, the linearity test of the data is linear and the Repeability Test is 0. The temperature sensor trainer is said to be valid as a learning medium after being validated by 2 validators, with a percentage of 100%. The feasibility level of the respondents was 96.44%, with the category